THE INFLUENCE OF ENGLISH SONG TOWARD STUDENTS’ VOCABULARY MASTERY AND STUDENTS’ MOTIVATION - Faliyanti, Eva (Premise: Journal of English Education and Applied Linguistics, 2017)
Learning vocabulary is the important aspect for the students when they are studying English. The students need fresh method to make them enjoy in learning process. The teacher should be able to deliver the material well. Using media appropriately is also needed for teachers. The objectives of this research are to know whether English song can improve the students’ vocabulary at the second semester of English education study program in University of Muhammadiyah Metro, to reveal whether English song English song influence the students’ motivation at the second semester of English education study program in learning process, to portray how much English song influence the students’ vocabulary mastery and students’ motivation at the second semester of English education study program in academic year 2015/2016. The population in this research is 40 students. It is consist 2 classes and each class consists of 20 students..The result of the data analysis proved that the value of t-test (tobs is 8,742 and ttable is 2,021). It means that tobs is higher than ttable(8,742>2,021). Based on the criteria for testing hypothesis was if the value of t obtained is higher than t table at significant level 0,05 the null hypothesis (Ho) is rejected and hypothesis alternative (HI) is accepted. After viewing the result of One Sample t-test, the writer came to conclusion that “there was significant Influence of English Song Toward Students’ Vocabulary Mastery and students’ motivation at the second semester of English education Study Program in the Muhammadiyah University of Metro Academic Year 2015/2016”.